2020
DOI: 10.1177/0363546520927015
|View full text |Cite
|
Sign up to set email alerts
|

A Combination Treatment of Raloxifene and Vitamin D Enhances Bone-to-Tendon Healing of the Rotator Cuff in a Rat Model

Abstract: Background: Tearing and degeneration of the rotator cuff at the tendon-to-bone junction are common in adults aged ≥50 years. Few studies have reported on the relationship between estrogen and the rotator cuff enthesis. In addition to preventing bone loss, selective estrogen receptor modulators have been shown to improve tendon and muscle quality. Purpose: To evaluate the effects of raloxifene (RLX) and vitamin D on rotator cuff tendon-to-bone healing in a rat model. Study Design: Controlled laboratory study. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…19,35 With respect to the recent studies of rotator cuffs, bone quality at the tendon insertion site of the humeral head has been determined to be an important factor that affects tendon-to-bone healing. 17,32,33,37,42 Tanaka et al 37 found that the estrogen-deficient state impaired bone quality at the repaired site as well as the biomechanical properties of the reattached rotator cuff of rats, causing worse tendon-to-bone healing. Shah et al 33 applied sclerostin antibody to increase bone quality and promote rotator cuff healing in a nonosteoporotic rat model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,35 With respect to the recent studies of rotator cuffs, bone quality at the tendon insertion site of the humeral head has been determined to be an important factor that affects tendon-to-bone healing. 17,32,33,37,42 Tanaka et al 37 found that the estrogen-deficient state impaired bone quality at the repaired site as well as the biomechanical properties of the reattached rotator cuff of rats, causing worse tendon-to-bone healing. Shah et al 33 applied sclerostin antibody to increase bone quality and promote rotator cuff healing in a nonosteoporotic rat model.…”
Section: Discussionmentioning
confidence: 99%
“…More than 250,000 cases require rotator cuff repair (RCR) annually, and the structural failure rates range from 9% to 94%. 9,15,17,32,33 Notably, in older patients with massive tears, the retear rate is alarmingly higher than that in young population. This may be caused by adverse biological ''healing environ-ments.''…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tanaka et al, 37 ovariectomized rats showed decreased biomechanical properties and poor development of chondroid tissue that influenced the repair of the tendon insertion postoperatively. Kim et al 14 reported that the combination treatment of raloxifene and vitamin D prevented a decrease in local bone mineral density and enhanced tendon-to-bone healing of the rotator cuff in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…However, adequate tendon‐bone healing is not always easily achieved and poses great challenges to patients and orthopaedic physicians. In the past few decades, a number of regenerative strategies have been developed to improve the process of tendon‐bone healing, including the delivery of growth factors 3 , 4 and stem cells 5 , 6 , as well as the use of various biomaterials 7 , 8 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%